Knowledge Workers & 'Ilm' - A Retrospective on Islamic Philosophy and Epistemology for Learning Organizations - Nasir, Nayab; Azhar, Sarwar M; Khan, Mumtaz (Journal of Management and Research, 2022)
Purpose - The current paper is intended to introduce knowledge workers and managers to a unique paradigm on virtue epistemology, that is, reflective knowledge, based on the doctrines of Islamic philosophy as 'Ilm.' The study proposed a holistic framework to acquire reflective knowledge, the epistemic attributes of knowledge workers, and the significance of reflective knowledge in the dynamic knowledge economy. Methodology – Theoretical framework proposed in the current paper is based on the theories proposed by Muslim philosophers. Books on the epistemological aspect of Islamic philosophy and web-based articles on Ilm as reflective knowledge were taken as references. Findings - Islamic philosophy helps to put forth a holistic paradigm on the virtues of knowledge workers and the attributes that help learning organizations acquire reflective knowledge. Practical Implications - The propositions made in this paper may be tested for empirical evidence in future research. Moreover, the framework to acquire reflective knowledge and instilling epistemic virtues in knowledge workers may be a powerful tool for knowledge managers. Originality/Value - Islamic philosophy is based on theological grounds; however, this paper intends to introduce the doctrines based on logic and rationale, proposed by noted scholars. The current study is also unique in constructing a holistic framework that may assist organizations to acquire reflective knowledge and train knowledge workers to acquire prescribed epistemic attributes.